Influence of adsorption and anaerobic granular sludge characteristics on long chain fatty acids inhibition process - Palatsi, J. (2012)
The impact of LCFA adsorption on the methanogenic activity was evaluated in batch assays for two anaerobic granular sludges in the presence and absence of bentonite as synthetic adsorbent. A clear inhibitory effect at an oleate (C18:1) concentration of 0.5 g(C18:1) L(-1) was observed for both sludges. Palmitate (C16:0) was confirmed to be the main intermediate of C18:1 degradation in not adapted sludge and its accumulation was further evidenced by fluorescence staining and microscopy techniques. LCFA inhibition could be decreased by the addition of bentonite, reducing the lag-phase and accelerating the kinetics of LCFA degradation, concluding in the importance of the adsorptive nature of the LCFA inhibitory process. Granule morphology and molecular profiling of predominant microorganisms revealed that biomass adaptation to LCFA could modify the intermediates accumulation profiles and process rates.